Biorrefinaria: investigação de processos físico-químico, fermentativo e térmico para o aproveitamento de serragem de eucalipto - Cardoso, André de Lima (2009)
With the increasing worldwide concern on the environmental impacts of the intensive use of oil derivatives, renewed and continuous efforts have been made to develop alternative technologies for the use of renewable resources in order to produce fuels as well as chemical and petrochemical derivatives. In this study, the use of different technologies applied in biorefinaries (thermal, physical-chemical and biotechnological processes) in a bench scale for a better utilization of forestry waste from eucalyptus sawdust was investigated. Since the pyrolytic thermal process has already been developed, we focused on the separation (liquid-liquid extraction) and the quantification processes (GC-MS) of compounds of the fine chemistry present in the bio-oil from pyrolysys. Results confirm the good performance of the separation and quantification techniques proposed. In addition to the characteristics of the oily fraction, the adsorption capacity of the pyrolytic coal through the measures of BET surface area, the interpretation of isotherms of Langmuir and Freundlich, iodine number index, and scanning electron microscopy (SEM) was investigated. Samples of solid waste, activated with the steam system built by hand, present adsorbent properties similar to the commerciallyproduced active coal. In the application of the physical-chemical process, the acid hydrolysis process was developed under pressure in Teflon containers for the generation of glucose and levulinic acid, which were quantified by PAP glucose and LC-MS/MS assays, respectively. Production, temperature and time parameters were adjusted (optimized) using the methodology of response surface. The resulting hydrolyzate, which showed low levels of glucose, did not offer support for the production of bioethanol; however, it may be an important source of levulinic acid. The solid residue obtained at this stage, characterized as lignin by infrared spectroscopy, showed a higher percentage of marketable lignols in the oily fraction obtained by pyrolysis when compared to bio-oil obtained directly from the sawdust. In the biotechnological process, the hydrolyzed sawdust extract was sent to fermentation with Candida guilhermondii for xylitol production, which is a saccharide with wide industrial application. Findings, based on the methodology of response surface, show a significant influence of time on the fermentation process developed. The maximum content of sugar determined by LC-MS/MS was achieved at mean temperatures. The processes developed were in general effective in the use of forest waste eucalyptus sawdust. Our results are a small contribution to the research of converting biomass and its waste materials in clean fuels, renewable inputs, and green products for the fine chemical, petrochemical, and pharmaceutical industries according to the precepts of biorefineries.